2019
DOI: 10.5539/ies.v12n2p100
|View full text |Cite
|
Sign up to set email alerts
|

Contributions Management of Parenting and Education Program to Strengthen the Service Three Early Childhood Education Center

Abstract: Early age is a “golden moment” which will not be repeated in the period of child development. A rare opportunity must be utilized to provide the best education and care in three centers, namely; school, family and community environment. The purpose of this research is to; 1) Describe the contribution of parenting education management; and 2) Describe the practice of parenting education in three education centers. This research method uses a qualitative approach with a multi-case study design. These informants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
0
9
1
4
Order By: Relevance
“…This finding showed a contrast with the study from Hariawan et al (2019) who found that Indonesian families believe that schools are responsible of their children's learning instead of shared responsibility between families and schools. The difference in findings can be due to the different level of education of the parents.…”
Section: Indonesian Parents' Concerns About Their Childrencontrasting
confidence: 89%
See 3 more Smart Citations
“…This finding showed a contrast with the study from Hariawan et al (2019) who found that Indonesian families believe that schools are responsible of their children's learning instead of shared responsibility between families and schools. The difference in findings can be due to the different level of education of the parents.…”
Section: Indonesian Parents' Concerns About Their Childrencontrasting
confidence: 89%
“…In the context of Indonesia, a study conducted by Hariawan, et al, (2019) in two early childhood education centers in Indonesia found that Indonesian families believe that schools have the main responsibility to ensure the academic success of their children. Parents' responsibility was paying the educational costs (Hariawan et al, 2019).…”
Section: Family-school Partnerships In Early Childhood Education Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…Anak didik di TK termasuk dalam usia emas perkembangan, pada rentang usia 4 sampai dengan 6 tahun yang sejak lahir memiliki miliaran sel neuron yang harus terhubung dalam otaknya. Synopsis yang terjadi antar sel neuron pada masa golden age anak dapat mencapai perkembangan maksimal jika dilakukan sesuai dengan tahapan perkembangan secara berkesinambungan (Hariawan et al, 2019). Stimulus yang dilakukan melalui proses pengalaman belajar sambil bermain ini menjadi momen yang berharga untuk menanamkan pemahaman tentang mitigasi bencana sejak dini, maka memilih dan menentukan strategi pendidikan anak usia dini dapat mempermudah penyampaian informasi kepada peserta, sebagaimana yang disampaikan Nuraeni (2014) bahwa strategi pendidikan anak usia dini dapat dilakukan secara bersama-sama lingkungan sekolah, lingkungan keluarga, dan lingkungan masyarkat.…”
Section: Pendidikan Mitigasi Bencana Bagi Anak Usia Dini Pada Paudunclassified